Age at first use of alcohol and risk of heavy alcohol use: A population-based study - Liang, Wenbin; Chikritzhs, Tanya (Hindawi Publishing Corporation, 2013)
Aim: To examine the association between age at first alcohol use and risk of heavy alcohol use among the adult US general drinking population.Methods: This population-based study used the 2010 National Survey on Drug Use and Health (NSDUH) from United States. Multivariate Poisson regression was employed to predict the frequency of heavy alcohol use (five or more drinks per occasion) in the last 30 days with age at first use of alcohol controlling for potential confounding factors.Results: Younger age at first use of alcohol was associated with increased likelihood of heavy alcohol use in the last 30 days in this population-based sample. This association remained significant when analysis was reperformed for the subgroup of participants who were with desired good health status and Kessler score lower than 12.Conclusion: Younger age at first use of alcohol was associated with increased likelihood of heavy alcohol use.